Colour, class and community : the Natal Indian Congress, 1971-1994 - Desai, Ashwin; Vahed, Goolam H., 1961- (Wits University Press, 2021)
Following a hiatus in the 1960s, the Natal Indian Congress (NIC) in South Africa was revived in 1971. In fascinating detail, Ashwin Desai and Goolam Vahed bring the inner workings of the NIC to life against the canvas of major political developments in South Africa during the 1970s and 1980s, and up to the first democratic elections in 1994. The NIC was relaunched during the rise of the Black Consciousness Movement, which attracted a following among Indian university students, and whose invocation of Indians as Black led to a major debate about ethnic organisations such as the NIC. This debate persisted in the 1980s with the rise of the United Democratic Front and its commitment to non-racialism. The NIC was central to other major debates of the period, most significantly the lines drawn between boycotting and participating in government-created structures such as the Tri-Cameral Parliament. Despite threats of banning and incarceration, the NIC kept attracting recruits who encouraged the development of community organisations, such as students radicalised by the 1980s education boycotts and civic protests. Colour, Class and Community, The Natal Indian Congress, 1971--1994 details how some members of the NIC played dual roles, as members of a legal organisation and as allies of the African National Congress' underground armed struggle. Drawing on varied sources, including oral interviews, newspaper reports, and minutes of organisational meetings, this in-depth study tells a largely untold history, challenging existing narratives around Indian 'cabalism', and bringing the African and Indian political story into present debates about race, class and nation.